BCAA supplementation enhances milk fat synthesis in Yili mares and promotes foal growth through remodeling of intestinal amino acid metabolism - Meng, Chen; Zeng, Yaqi; Wang, Jianwen; Yao, Xinkui; Meng, Jun (Frontiers in Microbiology, 2025)
IntroductionThis study evaluated the effects of graded supplementation of branched-chain amino acids (BCAAs) in lactating mares on lactation performance, foal growth, and metabolic responses.MethodsTwenty mare-foal pairs were assigned to control, low- (38 g/d), medium- (76 g/d), or high-dose (114 g/d) groups. Milk and blood samples were collected over 60 days for composition, hormone, and metabolomic analyses. Fecal microbiota from the foals was also examined.ResultsBCAAs supplementation interacted with lactation stage, enhancing milk fat yield and increasing milk growth hormone and progesterone. The medium dose (76 g/d) was effective, while 114 g/d showed the strongest effects. High-dose BCAAs altered organic acid abundance, influencing lipid, energy, and BCAA metabolism, correlating with milk composition changes. In foals, altered milk reduced serum BCAAs and other amino acids but elevated growth hormones (GH, INS, IGF-1) dose-dependently. Antioxidant and immune parameters were unaffected. The high dose increased blood urea nitrogen, indicating higher nitrogen load, whereas the medium dose supported growth without metabolic stress. Fecal microbiota analysis revealed enriched amino acid degradation pathways, especially for BCAAs.DiscussionWe conclude that BCAAs supplementation regulates milk fat synthesis and promotes foal growth via a milk–microbiota–metabolism axis, providing a basis for improving milk quality and offspring development through maternal nutrition.